Trends in perinatal health in metropolitan France from 1995 to 2016: Results from the French National Perinatal Surveys - Blondel, B.; Coulm, B.; Bonnet, C.; Goffinet, F.; Le Ray, C. (Journal of gynecology obstetrics and human reproduction, 2017)
To study trends in the main indicators of perinatal health, medical practices and risk factors in France since 1995. All live births during one week in 1995 (n=13,318), 2003 (n=14,737), 2010 (n=14,903) and 2016 (n=13,384). Data were from interviews of women in postpartum wards and from medical records and were compared between years. Between 1995 and 2016, maternal age and body mass index increased steadily. Pregnancies that occurred with use of contraception increased from 7.4% in 2010 to 9.3% in 2016. Smoking during pregnancy (16.6%) did not decrease since 2010. The frequency of more than three ultrasounds during pregnancy was 48.5% in 1995 and 74.7% in 2016. Deliveries in large public hospitals increased steadily. The caesarean section rate has been relatively stable since 2003 (20.4% in 2003, 21.1% in 2010 and 20.4% in 2016). The rate of induction of labour was 22% in 2010 and 2016. Overall, 83.8% of women had epidural analgesia/anaesthesia in 2016. Rates of pre-term birth in 2016 ranged from 7.5% among all live births to 6.0% among live born singletons; for singletons, this rate increased steadily from 1995 to 2016, whereas there was no clear trend for low birth weight. Exclusive breastfeeding decreased from 60.3% in 2010 to 52.2% in 2016. Routine national perinatal surveys highlight successful policies and recommendations but also point out some health indicators, practices, preventive behaviours and risk factors that need special attention.